The effect of different schedules of action observation training and motor imagery training on the changes in mental representation structure and skill performance - Kim, T.; Frank, C.; Schack, T. (International Journal of Sport Psychology, 2022)
Action observation (AO) training and motor imagery (MI) training have long been used independently as effective training methods to facilitate skill acquisition and learning. Recently, neurophysiological and behavioral studies on AO+MI training have shown that combinations of AO+MI training may be more effective than AO or MI training alone. However, the optimal scheduling of AO+MI training remains to be fully explored. Therefore, the purpose of this study was to examine the effect of different AO+MI training schedules of Taekwondo Poomsae on the changes in the structure formation of mental representations in long-term memory and motor variables over the course of learning. Forty participants with no previous experience in Taekwondo were randomly assigned to one of four groups: simultane- ous training group (AO+MI, AO+MI, …), alternate training group (AO, MI, AO, MI, …), blocked training group (AO, AO, …, MI, MI, …), and no-training group. Participants practiced the Taekwondo Poomsae thirty trials a day for three days of training. Mental representation structure and skill performance were measured be- fore and after three days of training as well as after a retention interval of one day. The results of this study showed that the three different AO+MI training improved mental representation structure and skill performance. In particular, the effect of alternate AO+MI training was relatively stronger. Taken together, the findings of this study suggest that simultaneous, alternate, and blocked AO+MI can be used as effective training schedules for enhancing the learning of a sequential motor skill, among which alternate AO+MI training schedule may be more effective.